Multiharmonic Toroidal Standing Alfvén Waves in the Midnight Sector Observed During a Geomagnetically Quiet Period. Issue 3 (16th March 2020) - Takahashi, Kazue; Vellante, Massimo; Del Corpo, Alfredo; Claudepierre, Seth G.; Kletzing, Craig; Wygant, John; Koga, Kiyokazu
Abstract: Excitation of toroidal mode standing Alfvén waves in the midnight sector of the inner magnetosphere in association with substorms is well documented, but studies are sparse on dayside sources for the waves. This paper reports observation of midnight toroidal waves by the Van Allen Probe B spacecraft during a geomagnetically quiet period on 12–13 May 2013. The spacecraft detected toroidal waves excited at odd harmonics below 30 mHz as it moved within the plasmasphere from ∼ 2100 magnetic local time to ∼ 0030 magnetic local time through midnight in the dipole L range 4.2–6.1. The frequencies and the relationship between the electric and magnetic field components of the waves are consistent with theoretical toroidal waves for a reflecting ionosphere. At the time of the nightside toroidal waves, compressional waves were observed by geostationary satellites located on the dayside, and the amplitudes of both types of waves varied with the cone angle of the interplanetary magnetic field. The nightside toroidal waves were likely driven by fast mode waves that resulted from transmission of upstream ultralow frequency waves into the magnetosphere. Ground magnetometers located near the footprint of the spacecraft did not detect toroidal waves. Key Points: Multiharmonic toroidal standing Alfvén waves were detected in the midnight sector of the plasmasphere Interplanetary magnetic field cone angle was small, which suggests that foreshock ULF waves were the energy source The toroidal waves were not detected on the ground at stations located in the midnight sector